Implementasi Program Pembiasaan Berbasis Keagamaan Dalam Rangka Penanaman Karakter di SMPN 2 Teras - Vida Afra Nur Annisa; Mohammad Zakki Azzani (STAI Terpadu Yogyakarta, 2024)
To improve the quality of education in Indonesia, educational institutions are starting to integrate learning with habituation. This research aims to describe implementing a religious-based habituation program in the context of cultivating character at SMP N 2 Teras. This type of research is descriptive qualitative with an interview approach to Islamic Religious Education (PAI) teachers. The research results show that character cultivation can be done through habituation activities. The habituation activities themselves include daily, weekly, and annual religious habituation activities. (1) Daily habituation activities include praying before starting learning, and midday prayer in congregation. (2) Weekly activities include familiarization with Al-Qur'an literacy activities and (3) Annual activities to commemorate Islamic holidays. Through these activities, characters can be instilled, including being friendly and communicative, disciplined and punctual, highly curious, honest, and always conveying things according to the facts. The main aim of holding religious habituation activities is to form a good character or person or in other words have commendable morals.